2015
DOI: 10.1108/ijcthr-04-2014-0033
|View full text |Cite
|
Sign up to set email alerts
|

How golf players’ satisfaction from golf experience predicts their loyalty intentions? Mediating role of perceived value

Abstract: Purpose – This study aims to evaluate the perceptions and behavioral intentions of golf players by means of the relationship between customer satisfaction, perceived value and loyalty concepts. Design/methodology/approach – The data used in testing the hypothesis developed were gathered by face-to-face survey method from the golf players using four golf courses in Antalya, Turkey during the peak season (March, April, May, October). At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…From the perspective of the TRA, this study has provided general measures to identify the golfers’ perceptions of employee attitudes (e.g., golf-course employees are glad to have golf tourists), destination attributes (e.g., cultural activities), and the individual preferences of golf tourists (e.g., emotional connections). These results are generally in line with the study on the characteristics of golf courses in Portugal (Correia et al, 2007) and on individual preferences and the perceived value of golf courses in Turkey (Akinci et al, 2015). Thus, the empirical findings based on Hainan Island in China in this study could shed some light on golf tourists’ travel planning regarding their selection of a specific destination and thereby further extend the golf tourism literature.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…From the perspective of the TRA, this study has provided general measures to identify the golfers’ perceptions of employee attitudes (e.g., golf-course employees are glad to have golf tourists), destination attributes (e.g., cultural activities), and the individual preferences of golf tourists (e.g., emotional connections). These results are generally in line with the study on the characteristics of golf courses in Portugal (Correia et al, 2007) and on individual preferences and the perceived value of golf courses in Turkey (Akinci et al, 2015). Thus, the empirical findings based on Hainan Island in China in this study could shed some light on golf tourists’ travel planning regarding their selection of a specific destination and thereby further extend the golf tourism literature.…”
Section: Discussionsupporting
confidence: 88%
“…Golfers might visit or revisit a golf destination for a variety of reasons (Correia et al, 2007; Hutchinson et al, 2010). Loyalty to the destination has been widely defined as a determinant of golfers’ future behavior (Akinci et al, 2015; Song et al, 2017). However, the role of golf-course employees and their attitudes to the golfers are becoming increasingly important for business success, but these aspects have not been fully examined in previous studies (García-Almeida et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This research result also supports previous research conducted by Akinci et al [38] stating that experience level perceived by tourist emotionally influences the perceived value, which will lead to higher tourist loyalty. This research result also proves the result of research conducted by Wu, Li, and Li [39] that experiential marketing significantly influences perceived value.…”
Section: Experiential Marketing's Influence On Customer Loyalty Through Perceived Valuesupporting
confidence: 91%
“…Experience and perceived value have been widely discussed in relation to service; however, to date, no research has identified the causal tie between these two constructs [19]. Some studies advocating an experience-perceived value relationship have regarded perceived value and experience as antecedents for behavioral outcomes [2,20]; however, some earlier research [21,22] suggested that experience directly influenced behavioral outcomes, with perceived value functioning only as a determinant.…”
Section: Participantsmentioning
confidence: 99%